A neural signature of exposure to masked faces after 18 months of COVID-19. (9th September 2022) - Prete, Giulia; D'Anselmo, Anita; Tommasi, Luca
Abstract: In the last two years, face-to-face interactions have drastically changed worldwide, because of the COVID-19 pandemic: the persistent use of masks has had the advantage of reducing viral transmission, but it has also had the cost of impacting on the perception and recognition of social information from faces, especially emotions. To assess the cerebral counterpart to this condition, we carried out an EEG experiment, extracting Event-Related Potentials (ERPs) evoked by emotional faces with and without surgical masks. Besides the expected impairment in emotion recognition in both accuracy and response times, also the classical face-related ERPs (N170 and P2) are altered by the presence of surgical masks. Importantly, the effect is stronger in individuals with a lower daily exposure to masks, suggesting that the brain must adapt to an extra constraint in decoding social input, due to masks hiding crucial facial information. Highlights: We measured changes in brain activity for emotional faces wearing surgical masks. Results confirmed an impairment in the recognition of emotions from masked faces. Face-related ERPs were altered by surgical masks. Participants less (vs more) exposed to masks showed different brain responses to faces. Our brain is (mal-)adapting to seeing masked faces due to COVID-19 pandemic constraints.